A pilot study exploring the quadratic nature of the relationship of strength to performance among shot putters - Simon, L.; Wanless, E.; Thrasher, A.; Judge, L.; Bellar, D.; Hindawi, O. S. (International Journal of Exercise Science, 2013)
The purpose of this pilot study was to examine the quadratic nature of the relationship between the strength and throwing distance in the shot put. A survey was sent to throws coaches with Master Coach or USA Track and Field Level III distinction to examine fifty-three collegiate and elite throwers (24 male, 29 female). The coaches reported the thrower`s personal best shot put distance and preseason weight room 1RM for bench press, power clean, and squat exercises. Relationship between distance and 1RM was determined via general linear model polynomial contrast analysis and regression. Data analysis showed significant linear and quadratic trends for distance and 1RM power clean for both male (linear: p</=0.001, quadratic: p=0.003) and female (linear: p</=0.001, quadratic: p</=0.001) elite and collegiate shot put athletes. Analysis also provided a quadratic equation to compare personal best distance and 1RM power clean. The power clean was found to be more closely related to shot put distance as compared with squat and also with bench press, which is the least related. Based on the results of this investigation, in addition to strength exercises such as the squat and bench press, power exercises such as the power clean should also be incorporated into strength and conditioning programs of shot put athletes for optimal performance.